Critique of The Philosophy of Science on The Effectiveness of Digital Transactions - Riansyah, Bima; Triyatno, Ghazy; Dewi Masitoh; Saffanah Az Zahra (Universitas Wahid Hasyim Semarang, 2025)
Digital transactions utilize a digitized system, providing easy access for economic actors and making them an effective transactional method. This study aims to analyze the effectiveness of digital transactions through the lens of the philosophy of science. Digital transactions, as an innovation of conventional transactions, have provided accessibility and efficiency in economic activities. However, alongside their benefits, digital transactions also face challenges such as cybercrime, low digital literacy, and weak legal protection. The research employs a qualitative method with a literature review approach, collecting and analyzing data from various literature sources. The findings indicate that digital transactions are not yet fully effective due to weaknesses in security systems, public literacy, and legal regulations. The philosophical analysis reveals that digital transactions need to be integrated with moral and ethical principles to achieve optimal effectiveness. This study provides recommendations for service providers, users, and the government to enhance security, education, and regulations in digital transactions.